2015
DOI: 10.1111/acel.12412
|View full text |Cite
|
Sign up to set email alerts
|

Age modifies respiratory complex I and protein homeostasis in a muscle type‐specific manner

Abstract: SummaryChanges in mitochondrial function with age vary between different muscle types, and mechanisms underlying this variation remain poorly defined. We examined whether the rate of mitochondrial protein turnover contributes to this variation. Using heavy label proteomics, we measured mitochondrial protein turnover and abundance in slow‐twitch soleus (SOL) and fast‐twitch extensor digitorum longus (EDL) from young and aged mice. We found that mitochondrial proteins were longer lived in EDL than SOL at both ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 47 publications
(68 reference statements)
7
64
3
Order By: Relevance
“…Data for our exercised muscle accords with previous reports in young rodents (aged 11–28 weeks), where prolonged voluntary wheel running (unloaded) for 4 to 20 weeks increased key markers of mitochondrial biogenesis, oxidative phosphorylation, and intramuscular mitochondrial content [27, 28]. Skeletal muscles rely on mitochondria to meet the higher demand for ATP generated during sustained contractile activity, and both mitochondrial content and function greatly impact muscle performance [63]. Many studies in middle-aged and old rodents demonstrate that mice [6668] and rats [6971] of both sexes (aged 13–32 months) maintain the ability to increase muscle mitochondrial enzymes through forced or voluntary exercise, despite older mice running lower maximum daily distances (old <1 km and young >10 km per day) [66].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Data for our exercised muscle accords with previous reports in young rodents (aged 11–28 weeks), where prolonged voluntary wheel running (unloaded) for 4 to 20 weeks increased key markers of mitochondrial biogenesis, oxidative phosphorylation, and intramuscular mitochondrial content [27, 28]. Skeletal muscles rely on mitochondria to meet the higher demand for ATP generated during sustained contractile activity, and both mitochondrial content and function greatly impact muscle performance [63]. Many studies in middle-aged and old rodents demonstrate that mice [6668] and rats [6971] of both sexes (aged 13–32 months) maintain the ability to increase muscle mitochondrial enzymes through forced or voluntary exercise, despite older mice running lower maximum daily distances (old <1 km and young >10 km per day) [66].…”
Section: Discussionsupporting
confidence: 87%
“…While a variety of mitochondrial abnormalities become more common in the sarcopenic muscles [63], in the present study, no changes to CS activity were observed (used as an indicator of mitochondrial density) between middle (15 months) and old (23 months) age groups. Our results accord with those of Jackson et al (2011) who reported unchanged CS activity in the gastrocnemius muscles between middle and old age (18 and 28 months) C57BL/6J mice [64].…”
Section: Discussioncontrasting
confidence: 67%
“…Consistently, the activity of both complexes I and II were elevated in the studies that demonstrated increased mitochondrial biogenesis and content in skeletal muscle (Menshikova et al, 2006). The different physiology of muscle and brain cells may contribute, although a recent study showed that complex I linked mitochondrial function was also affected by aging in muscle (Kruse et al, 2016). Local augmentation of mitochondrial mass would allow skeletal muscle to perform a larger proportion of work by aerobic rather than anaerobic metabolism, as less ADP would be required to stimulate the same degree of mitochondrial respiration (Constable et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of altered redox homeostasis in loss of neuromuscular integrity and function with ageing has been investigated in several murine models, which have undergone genetic modifications of redox signalling/homeostasis components 19, 23, 25, 29, 30, 31, 32, 33, 34, 240, 241, 242. Transgenic murine models have provided insight into the importance of RONS regulatory systems in lifespan and neuromuscular ageing, and it has been reported that SOD2 −/− ,243 GRX3 −/− ,244 GPX4 −/− ,245 TRX1 −/− ,246 TRX2 −/− ,247 TR1 −/− 248 and TR2 −/− 249 murine models are embryonically lethal.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 99%
“…Targeted overexpression of the human CAT gene to mitochondria in the mCAT tg model has shown to protect against age‐induced deficits in muscle mitochondrial function, improve skeletal muscle respiratory function with age,19, 242 improve voluntary exercise and decrease the intracellular Ca 2+ leak and the level of oxidized ryanodine receptor 132. This occurs likely due to the attenuation of mito‐H 2 O 2 which potentially reduces the reliance on antioxidant coupled NADPH‐driven reduction of oxidants in the mitochondria, thereby maintaining a higher availability of NADPH for exogenous antioxidant reduction 280…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 99%